2022
DOI: 10.3389/fphar.2022.970400
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin derivative DHA27 enhances the antibacterial effect of aminoglycosides against Pseudomonas aeruginosa by inhibiting mRNA expression of aminoglycoside-modifying enzymes

Abstract: Bacterial resistance is becoming increasingly serious, the present study aimed to investigate the mechanism of antibacterial sensitization effect of DHA27 combined with tobramycin in tobramycin-resistant Pseudomonas aeruginosa (PA). We found that DHA27 combined with aminoglycosides had an antibacterial sensitization effect on PA. Tobramycin, owing to its lower toxic and side effects, was selected to further study the molecular mechanism of drug combination. A sublethal-dose bacterial challenge/sepsis mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Though, not as common as in tRNA, rRNA contain numerous distinct types of post-transcriptional modifications, especially rRNA methylation. Research has shown that rRNA methylation can impact antibiotic resistance development, as many antibiotic targets are located on the ribosome and ncRNAs frequently adopt central roles in regulatory networks ( Laughlin et al., 2022 ; Wang et al., 2022 ; Papenfort and Melamed, 2023 ). Of those, RNA methylation and ncRNAs modification have been reported as the most frequent type of modification in a wide range of bacteria ( Table 1 ).…”
Section: What Is Epigenetics?mentioning
confidence: 99%
“…Though, not as common as in tRNA, rRNA contain numerous distinct types of post-transcriptional modifications, especially rRNA methylation. Research has shown that rRNA methylation can impact antibiotic resistance development, as many antibiotic targets are located on the ribosome and ncRNAs frequently adopt central roles in regulatory networks ( Laughlin et al., 2022 ; Wang et al., 2022 ; Papenfort and Melamed, 2023 ). Of those, RNA methylation and ncRNAs modification have been reported as the most frequent type of modification in a wide range of bacteria ( Table 1 ).…”
Section: What Is Epigenetics?mentioning
confidence: 99%